Caloric restriction upregulates the expression of DNMT3.1, lacking the conserved catalytic domain, in Daphnia magna. Issue 12 (18th November 2020) - Nguyen, Nhan Duc; Matsuura, Tomoaki; Kato, Yasuhiko; Watanabe, Hajime
Summary: DNA methylation plays an important role in many aspects of biology, including development, disease, and phenotypic plasticity. In the branchiopod crustacean, Daphnia, de novo DNA methylation has been detected in specific environmental contexts. However, fundamental information on de novo DNA methyltransferase DNMT3 orthologs, including domain organization, developmental expression, and response to environmental stimuli, is lacking. In this study, we examined two DNMT3 orthologs in Daphnia magna, DapmaDNMT3.1 and DapmaDNMT3.2. Amino acid sequence alignment revealed that DapmaDNMT3.1 and DapmaDNMT3.2 lack the conserved methyltransferase motifs of the catalytic domain and the PWWP domain, respectively. We profiled the expression of the two orthologs during embryogenesis and under various feeding levels. During embryogenesis, in contrast to the low DapmaDNMT3 . 1 expression, DapmaDNTM3 . 2 was highly expressed at specific stages, that is, in the one cell‐stage and at 48 hr post ovulation. In nutrient‐rich condition, both genes were lowly expressed, whereas DapmaDNMT3 . 1 was upregulated at the lower food levels, suggesting a potential role of DapmaDNMT3 . 1 in gene regulation in response to caloric restriction. These findings provide a basis for understanding the developmental stage‐ and stress‐dependent function of DNMT3 orthologs in D . magna .